Narrative Structure of the Dayak Benuaq Folktale ‘Pohon Berdaun Kain’: A Proppian Analysis - Miranda Bella; Nina Queena Hadi Putri; Rokhmansyah Alfian; Nia Novita Putri (MASI Mandiri Edukasi, 2026)
Folktales function not only as entertainment but also as cultural mechanisms for transmitting values and legitimizing social norms. However, structural studies of Kalimantan folklore, particularly those applying Vladimir Propp’s morphological approach, remain limited. This gap indicates the need for systematic analysis to reveal the narrative patterns underlying local folktales. This study aims to analyze the narrative structure of the Dayak Benuaq folktale Pohon Berdaun Kain using Vladimir Propp’s morphology. This research employs a qualitative descriptive method with a textual analysis design. The data were obtained from the book Cerita Rakyat Kabupaten Kutai Barat, published by the East Kalimantan Language Center. The results show that only 9 out of Propp’s 31 narrative functions are realized, forming a double-move narrative pattern. The structure develops from the resolution of personal conflict to the establishment of collective moral legitimacy through the distribution of magical agents, transformation, and punishment. Several spheres of action experience reduction and shifts, including the absence of the false hero function and the symbolic transformation of the princess and father roles. These findings demonstrate that Propp’s morphology is adaptive and relevant for analyzing Indonesian folklore, particularly in revealing how narrative structures function as mechanisms for reproducing social values. This study contributes to the development of folklore studies and structuralism by providing empirical evidence from the Dayak Benuaq cultural context.